Blackpentecostal breath : the aesthetics of possibility / Ashon T. Crawley. - Crawley, Ashon T. (Commonalities., 2017)
'Blackpentecostal Breath' investigates the relationship of aesthetic productions to modes of collective, social intellectual practice. Engaging black studies, queer theory, sound studies, literary theory, theological studies, continental philosophy and visual studies, this work analyzes the ways otherwise modes of existence are disruptions of marginalization and violence.